2011
DOI: 10.1371/journal.pone.0018959
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc-Specific Antibody CTD110.6 Cross-Reacts with N-GlcNAc2-Modified Proteins Induced under Glucose Deprivation

Abstract: Modification of serine and threonine residues in proteins by O-linked β-N-acetylgulcosamine (O-GlcNAc) glycosylation is a feature of many cellular responses to the nutritional state and to stress. O-GlcNAc modification is reversibly regulated by O-linked β-N-acetylgulcosamine transferase (OGT) and β-D-N-acetylgulcosaminase (O-GlcNAcase). O-GlcNAc modification of proteins is dependent on the concentration of uridine 5′-diphospho-N-acetylgulcosamine (UDP-GlcNAc), which is a substrate of OGT and is synthesized vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 23 publications
12
76
1
Order By: Relevance
“…1C). Furthermore, treatment of lysates from C2C12 myocytes following glucose deprivation, with PNGase F to remove N-glycans as previously described (33), resulted in only a modest decrease in intensity of CTD110.6 positive staining (Fig. 1D).…”
Section: Glucose Deprivation Increases O-glcnac Levels In a Timeand Dsupporting
confidence: 55%
See 2 more Smart Citations
“…1C). Furthermore, treatment of lysates from C2C12 myocytes following glucose deprivation, with PNGase F to remove N-glycans as previously described (33), resulted in only a modest decrease in intensity of CTD110.6 positive staining (Fig. 1D).…”
Section: Glucose Deprivation Increases O-glcnac Levels In a Timeand Dsupporting
confidence: 55%
“…Evaluation of Glucose Deprivation on N-Glycan Modification-Cells were treated with PNGase F to hydrolyze N-glycans by incubating lysates with 1/15 unit PNGase for 1 h at 37 ºC based on methods similar to those described previously (33). Concanavalin A (ConA) was obtained from GE Healthcare (17-0450-01).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a reconstituted lipid bilayer, it was demonstrated that the DLO flippase enables the bidirectional movement of DLOs with various oligosaccharide structures in the ER (6). This is also true in mammalian cultured cells, because GlcNAc 2 -PP-dolichol synthesized on the cytosolic side of the ER membrane is transferred to proteins (19). Therefore, the degradation of DLO intermediates (13,14) can theoretically occur on either side of the ER membrane.…”
Section: Discussionmentioning
confidence: 97%
“…Our results suggest that the pyrophosphatase-mediated degradation of premature DLOs functions as a quality control system to avoid abnormal N-glycosylation under conditions that impair efficient DLO biosynthesis. subset of glycoproteins (19). However, it remains largely unknown how glucose availability controls the biosynthesis of DLOs.…”
Section: Significancementioning
confidence: 99%